Performance of Local Rabbit ( Lepus nigricollis ) Given The Concentrate On Different Level With Feed Based On Waste of Carrot Leaf (Daucus carota L.) - I G. N. S. D., Pertiwi; Puger, A. W.; Nuriyasa, I M. (Jurnal Peternakan Tropika; Vol 6 No 3 (2018), 2018)
Research on the performance of local rabbits fed concentrate at different levels with carrot leaf base feed was conducted in Dajan Peken Village, Tabanan Subdistrict, Tabanan Regency were reread for 12 weeks. The design used in this research was a randomized block design, with five replications and used 20 unit object. The rabbits were allocated randomly into four treatments, namely rabbits is fed without concentrate (R0), concentrate of 15 g/head/day (R1), concentrate of 30 g/head/day (R2), concentrate of 45 g/head/day (R3). Carrots leaf and water fed ad_libitum . Results of the research, it was found that the rabbits with treatment of R3 consume least carrot leaf and consume more concentrate, so that weight gain and the body weight are the highest (p<0,05), while the obtained FCR is not significantly different from the other treatments. Performance of local rabbits fed control rations plus concentrate 45 g/head/day (R3) showed higher results from treatment of R0 (without concentrate) and the others treatments. Keywords: Local rabbits, concentrate, carrot leaf, performance